2023
DOI: 10.3390/math11092157
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Based Information Sharing Security for the Internet of Things

Abstract: The Blockchain (BCT) is the first decentralized ledger to include a trust mechanism in its design. It establishes a trustworthy framework for distributed commands by using data redundancy at several nodes. Conspicuously, the current study presents a BCT-based lightweight IoT information exchange security architecture for data exchange. The proposed technique uses a dual chain methodology, namely transaction and data BCT working together to provide distributed storage and tamper-proofing of data. Moreover, Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Within the context of the big data age, data sharing is gradually rising with the embodiment of data value. However, security problems such as centralized deployment, malicious theft, and tampering greatly affect the security of data [198]. Significant empirical evidence reveals that about 2.7 zettabytes of data in the digital universe are being threatened by cybercrime incidents that are on the rise globally.…”
Section: Sdg Key Challenge Cybersecurity Concernmentioning
confidence: 99%
“…Within the context of the big data age, data sharing is gradually rising with the embodiment of data value. However, security problems such as centralized deployment, malicious theft, and tampering greatly affect the security of data [198]. Significant empirical evidence reveals that about 2.7 zettabytes of data in the digital universe are being threatened by cybercrime incidents that are on the rise globally.…”
Section: Sdg Key Challenge Cybersecurity Concernmentioning
confidence: 99%
“…Many previous studies have found the close relationship between IoT data sharing and data privacy protection. Currently, the focus on data privacy protection is mainly in specific areas, such as the data analysis of patient conditions in the medical field [37], industry information [4] and data protection in the railway transportation sector [29]. There is relatively less coverage of privacy protection concerning multilingual data based on IoT news.…”
Section: Applications Of Privacy-preserving Multilingual Comparable C...mentioning
confidence: 99%
“…Paper Summary [3,6,22] Privacy protection practice for data mining and construction corpus for multiple data clustering; multilingual comparable corpus used in language teaching; evaluation of privacy-oriented corpus by use of text anonymization. [4,8,30,36] Privacy protection for medical data, industry data and railway data, less coverage of multilingual comparable data in IoT.…”
Section: Applications Of Privacy-preserving Multilingual Comparable C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Blockchain Name Block-Time Blockchain based QR code (13) 0.217secs Blockchain in transition system (21) 0.188 msecs Blockchain based information sharing Security (27) 1.254 ms Proposed <0.210 msecs…”
Section: Table 3 a Comparison Between The Existing Systems And The Pr...mentioning
confidence: 99%